2015
DOI: 10.1111/nmo.12668
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and non‐invasive in vivo effects of the cannabinoid‐1 receptor agonist AM841 on gastrointestinal motor function in the rat

Abstract: Background Cannabinoids have been traditionally used for the treatment of gastrointestinal (GI) symptoms, but the associated central effects, through cannabinoid-1 receptors (CB1R), constitute an important drawback. Our aims were to characterize the effects of the recently developed highly potent long-acting megagonist AM841 on GI motor function and to determine its central effects in rats. Methods Male Wistar rats were used for in vitro and in vivo studies. The effect of AM841 was tested on electrically-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…The high resolution X‐ray imaging utilized in this study provided clear localization of magnetic beads and allowed discrimination of the extent to which ingested contents had travelled over time, without the need for postmortem confirmation. This is a major technical advantage for future studies, building on previous X‐ray studies using liquid suspensions . We note the recent use of non‐invasive 3D X‐ray micro computed tomography imaging with contrasting metallic particles to assess gastric retention in rats …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The high resolution X‐ray imaging utilized in this study provided clear localization of magnetic beads and allowed discrimination of the extent to which ingested contents had travelled over time, without the need for postmortem confirmation. This is a major technical advantage for future studies, building on previous X‐ray studies using liquid suspensions . We note the recent use of non‐invasive 3D X‐ray micro computed tomography imaging with contrasting metallic particles to assess gastric retention in rats …”
Section: Discussionmentioning
confidence: 98%
“…To study effective treatments to improve GI transit we require animal models of dysmotility that translate to humans and mimic the transit of solid foods. Many current methods to measure GI transit track the progress of liquid slurries which transit differently than solid foods. Furthermore, to determine GI transit to a particular location these methods require postmortem evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the activity of the endocannabinoid system varies between species and different regions of the GI tract within the same species, activation of CB 1 receptors coupled to cholinergic motor neurons has been found to inhibit excitatory neuromuscular transmission in human colonic circular muscle (Hinds et al, 2006) and inhibit colonic propulsion in mice and rat (Pinto et al, 2002; Abalo et al, 2015). In recent human trials, dronabinol, a non-selective cannabinoid receptor agonist, was found to inhibit colonic motility in both healthy subjects (Esfandyari et al, 2006, 2007) and patients with IBS-related diarrhea (IBS-D) (Wong et al, 2011).…”
Section: Emerging and Potential Treatments For Cid And Cicmentioning
confidence: 99%
“…In our study, using conscious rats, loperamide effects were clearly dose‐dependent and significant for all doses. The effects of Lop 1 and Lop 10 on gastrointestinal motility were comparable to those of the cannabinoid agonist AM841 at 0.1 and 0.5 mg kg −1 , respectively, where only AM841 at 0.5 mg kg −1 was able to induce significant antinociception, hypothermia, and catalepsy . At 10 mg kg −1 , morphine effects on gastrointestinal motility were not as intense as those of loperamide at the same dose .…”
Section: Discussionmentioning
confidence: 78%
“…Loperamide induced CNS effects at the highest dose tested in all tests except for catalepsy. Catalepsy is characteristically induced by antipsychotics and, less intensely, by cannabinoids, although the synthetic cannabinoid CB1 receptor agonist AM841 did not exert this or other central effects when used at relatively low doses, yet able to potently suppress gastrointestinal motility . Catalepsy may be induced by morphine, at large amounts (but mechanisms differ from those triggered by antipsychotics like haloperidol).…”
Section: Discussionmentioning
confidence: 99%